2022
DOI: 10.1002/ps.6901
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural regulator and molecular reception of a double‐edge‐sword hunter beetle

Abstract: BACKGROUND: The black carabid beetle Calosoma maximoviczi is a successful predator that serves as both a beneficial insect and a severe threat to economic herbivores. Its hunting technique relies heavily on olfaction, but the underlying mechanism has not been studied. Here, we report the electrophysiological, ecological and molecular traits of bioactive components identified from a comprehensive panel of natural odorants in the beetle-prey-plant system. The aim of this work was to investigate olfactory percept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…We found that beta-Caryophyllene had the lowest average binding energy (−9.99 kcal/mol) among the 46 ligands, and Methyl isothiocyanate had the highest average binding energy (−2.53 kcal/mol) (see Table S5 for details). Beta-Caryophyllene is associated with odorant recognition, which has been often reported in important Lepidoptera pests such as Spodoptera littoralis , Spodoptera exigua , Helicoverpa armigera , and Eriocrania semipurpurella [ 54 , 55 , 56 , 57 ], important Diptera pests such as Bactrocera dorsalis and Aedes aegypti [ 58 , 59 ], Hymenoptera insects such as Anastatus japonicas [ 60 ], Coleoptera insects such as Calosoma maximoviczi and Anthonomus rubi [ 61 , 62 ], and Hemiptera pests such as Adelphocoris lineolatus , Apolygus lucorum , and Diaphorina citri [ 63 , 64 , 65 ]. Methyl isothiocyanate is an important novel soil fumigant pesticide [ 66 , 67 ], which showed a low binding degree as expected.…”
Section: Resultsmentioning
confidence: 99%
“…We found that beta-Caryophyllene had the lowest average binding energy (−9.99 kcal/mol) among the 46 ligands, and Methyl isothiocyanate had the highest average binding energy (−2.53 kcal/mol) (see Table S5 for details). Beta-Caryophyllene is associated with odorant recognition, which has been often reported in important Lepidoptera pests such as Spodoptera littoralis , Spodoptera exigua , Helicoverpa armigera , and Eriocrania semipurpurella [ 54 , 55 , 56 , 57 ], important Diptera pests such as Bactrocera dorsalis and Aedes aegypti [ 58 , 59 ], Hymenoptera insects such as Anastatus japonicas [ 60 ], Coleoptera insects such as Calosoma maximoviczi and Anthonomus rubi [ 61 , 62 ], and Hemiptera pests such as Adelphocoris lineolatus , Apolygus lucorum , and Diaphorina citri [ 63 , 64 , 65 ]. Methyl isothiocyanate is an important novel soil fumigant pesticide [ 66 , 67 ], which showed a low binding degree as expected.…”
Section: Resultsmentioning
confidence: 99%
“…Some herbivore-infested plants produce tetradecane, which acts as kairomone to attract the pest’s natural enemies ( Li et al, 2022 ). It has been reported as an attractive plant volatile for several insect pests ( Mu et al, 2012 ; Mitra et al, 2020 ; Chen et al, 2022 ; Guo et al, 2022 ). There is, however, scant evidence from earlier investigations that it is an attractant for mirid bugs.…”
Section: Discussionmentioning
confidence: 99%
“…The binding patterns between the two CpomGOBP2 proteins and their odorant molecule ligands, as well as the key binding sites, were visualized using MOE. The detailed steps of molecular docking were described in the previous study [55].…”
Section: Modeling and Molecular Dockingmentioning
confidence: 99%